Association between Use of Methadone, Other Central Nervous System Depressants, and QTc Interval–Prolonging Medications and Risk of Mortality in a Large Cohort of Women Living with or at Risk for Human Immunodeficiency Virus Infection. Issue 9 (13th August 2019) - Tamraz, Bani; Reisner, Lori; French, Audrey L.; King, Samuel T.; Fischl, Margaret A.; Ofotokun, Igho; Kashuba, Angela; Milam, Joel; Murphy, Kerry; Augenbraun, Michael; Liu, Chenglong; Finley, Patrick R.; et al.
Abstract : Study Objective: To evaluate the association between use of methadone, other central nervous system (CNS) depressants, and QTc interval–prolonging medications and risk of mortality among human immunodeficiency virus (HIV)‐infected and at‐risk HIV‐uninfected women. Design: Multicenter, prospective, observational cohort study (Women's Interagency HIV Study [WIHS]). Participants: A total of 4150 women enrolled in the WIHS study between 1994 and 2014 who were infected (3119 women) or not infected (1031 women) with HIV. Measurements and Main Results: Data on medication utilization were collected from all study participants via interviewer‐administered surveys at 6‐month intervals (1994–2014). Mortality was confirmed by National Death Index data. With age defining the time scale for the analysis, Cox proportional hazards models were used to estimate hazard ratios (HRs) for all‐cause mortality in HIV‐infected and ‐uninfected women and non–acquired immunodeficiency syndrome (AIDS) deaths in HIV‐infected women. A total of 1046 deaths were identified, of which 429 were considered non‐AIDS deaths. Use of benzodiazepines, CNS depressants (excluding methadone), and number of medications with conditional QTc interval–prolonging effects were each associated with all‐cause mortality in multivariate models of HIV‐infected women: hazard ratio (HR) 1.28, 95% confidence interval (CI) 1.01–1.60, p=0.037; HR 1.61, 95% CI 1.35–1.92, p<0.0001; and HR 1.15 per drug, 95% CI 1.00–1.33, p=0.047, respectively. Other explanatory variables for all‐cause mortality in this model included HIV viral load, CD4 + cell count, renal function, hemoglobin and albumin levels, HIV treatment era, employment status, existence of depressive symptoms, ever use of injection drugs, and tobacco smoking. Of interest, use of CNS depressants (excluding methadone) was also associated with non‐AIDS deaths (HR 1.49, 95% CI 1.49–2.2, p<0.0001). Although use of benzodiazepines and conditional QT interval–prolonging medications were associated with increased risk of non‐AIDS mortality (HR 1.32 and 1.25, respectively), the effect was not statistically significant (p>0.05). Conclusion: In this cohort of HIV‐infected and at‐risk HIV‐uninfected women, use of benzodiazepines, CNS depressants, and conditional QTc interval–prolonging medications were associated with a higher risk of mortality independent of methadone and other well‐recognized mortality risk factors. Care must be taken to assess risk when prescribing these medications in this underserved and at‐risk patient population.